2020
DOI: 10.23975/bjvetr.2020.170615
|View full text |Cite
|
Sign up to set email alerts
|

Morphologcal and Molecular Study of Hard Ticks Species That Infested Small Ruminants in Duhok Governorate, Kurdistan Region, Iraq

Shameeran Salman Ismael,
Lokman Tayib Omer

Abstract: Ticks are harmful ectoparasite that feed on human and animal blood and causing many diseases through the world. They infested many hosts including: mammals, reptiles and birds.Ticks are important vector and they have the ability to transmit a variety of pathogenic agent to humans and animals. Ticks are divided into two major groups which are hard tick (Ixodidae) and soft tick (Argasidae). Because there was no such study done on identification of tick species by PCR technique in Kurdistan and particularly in Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…turanicus. This result is consistent with that reported byKadir et al (2012);Mohammad, (2016) andIsmael and Omer, (2020) in different governorates of Iraq Razmi and Yaghfoori (2013). andRamzan et al (2019) andAl-Hamidhi et al (2021) reported these species Ixodid ticks infested sheep in other countries such as Iran, and Saudi Arabia, respectively.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…turanicus. This result is consistent with that reported byKadir et al (2012);Mohammad, (2016) andIsmael and Omer, (2020) in different governorates of Iraq Razmi and Yaghfoori (2013). andRamzan et al (2019) andAl-Hamidhi et al (2021) reported these species Ixodid ticks infested sheep in other countries such as Iran, and Saudi Arabia, respectively.…”
supporting
confidence: 91%
“…Furthermore, OT in small ruminants causes a high morbidity rate reach to 100%, with a mortality rate of more than 46% (Tageldin et al, 2005;El Imam et al, 2015). There are several genes used for molecular detection of the T. ovis and T. lestoquardi such as Major merozoite piroplasm surface antigen (MMPSA) gene (Esmaelizad et al, 2011), 16S ribosomal ribonucleic acid (16S rRNA) gene (Ismael and Omer, 2020), 12S ribosomal ribonucleic acid (12S rRNA) gene (Azmi et al, 2019), small subunit ribosomal RNA (SSU rRNA) gene (Benedicto et al, 2020;Ceylan et al, 2021), and the more common gene is 18S ribosomal ribonucleic acid (18S rRNA) (Eliwa et al, 2021;Metwally et al, 2021). Ovine theileriosis can be diagnosed based on polymerase chain reaction (PCR) assay, it is an important technology in epidemiological and phylogenetic studies of Theileria spp.…”
Section: Introductionmentioning
confidence: 99%
“…Most cases of CCHF happen in rural areas where domestic and wild animals serve as tick hosts that play an important role in the spread of the virus in the environment. 37,38 In Duhok City, north of Iraq, a study done by Ismael and Omer 39 and Ismael and Omer 40 showed the most common species of hard ticks were Hyalomma, Boophilus, and Rhipicephalus ticks that infest both sheep and goats, and these results support the high outbreak of CCHF during 2020-2022. Finally, it is important to treat suspect individuals carefully if they have a history of tick bites or have a fever and skin rash in an area where the disease is endemic.…”
Section: Epidemiology Of Cchfmentioning
confidence: 82%
“…chaina1 and china 2, which are highly pathogenic hemoprotozoan, cause a malignant form of the disease called malignant ovine theileriosis (6,7). These parasites can be biologically transmission via Ixodidae ticks from the genera: Hyalomma, Haemaphysalis, and Rhipicephalus, Amblyomma (8)(9)(10), also can be mechanically transmission by stinging flies or blood-sucking insects and blood-contaminated syringes and needles (11,12), Moreover, through vertical transmission (Transplacental transmission) from the ewe to the fetus (9). Ovine theileriosis has been reported in various geographic regions, including Central Asia, North and East Africa, and Southern and Eastern Europe (13).…”
Section: Introductionmentioning
confidence: 99%